Answer:
- 1st person: $43
- 2nd person: $85
- 3rd person: $96
Explanation:
Let a, b, c represent the amounts received by the first, second, and third person, respectively.
2a-1 = b
c = b+11
a + b + c = 224
Substituting for c, we have ...
a + b + b+11 = 224
a +2b = 213
Substituting for b, we have ...
a +2(2a -1) = 213
a +4a -2 = 213 . . . . . eliminate parentheses
5a = 215 . . . . . . . . . . add 2
a = 43 . . . . . . . . . . . . .divide by 5
b = 2a -1 = 2(43) -1 = 85
c = b +11 = 85 +11 = 96
The amounts received were ...
- 1st person: $43
- 2nd person: $85
- 3rd person: $96